Factors affecting hotel managers' intentions to adopt robotic technologies: A global study. (April 2022) - Pizam, Abraham; Ozturk, Ahmet Bulent; Balderas-Cejudo, Adela; Buhalis, Dimitrios; Fuchs, Galia; Hara, Tadayuki; Meira, Jessica; Revilla, Mercedes Raquel García; Sethi, Deepa; Shen, Ye; State, Olimpia; Hacikara, Ahmet; et al.
Abstract: The objective of this study that was conducted with 1077 hotel managers in 11 countries in North and South America, Europe, Asia and the Middle East, was to identify the effects of technological, organizational, and environmental (TOE) factors on hotel managers' intentions to adopt robotic technologies in their hotels. Structural equation modeling (SEM) was utilized to test the study hypotheses. The results indicated that hotel managers' intention to adopt robotic technologies were positively influenced by their perceived relative advantage, competitive pressure and top management support and negatively influenced by their perceived complexity of the technology. The study results further demonstrated that the impacts of relative advantage, complexity, top management support, and competitive advantage on intention to adopt were moderated by innovativeness. The current study also addressed the theoretical and practical implications to existing knowledge and practice in the hotel industry. Highlights: TOE factors' impact on hotel managers' robotic technology adoption were examined. Relative advantage, competitive pressure, and top mgmt. support had positive impact. Complexity had a negative impact on intention to adopt robotic technologies. The moderating impact of innovativeness was significant.